Histological study of donor's duodenal mucosa biopsy specimens in the diagnosis of pancreatoduodenal complex rejection: the experience of N.V. Sklifosovsky Research Institute for Emergency Medicine - R. V. Storozhev; G. A. Nefedova; Yu. S. Teterin; G. P. Titova; I. V. Dmitriev; N. V. Borovkova; M. Sh. Khubutiya; А. V. Pinchuk (Трансплантология (Москва))
Background. The verification and identification of the transplanted pancreas rejection type requires a morphological examination of the graft tissue. The pancreas graft transcutaneous biopsy procedure is associated with a high risk of surgical and infectious complications, and with the risk of the graft loss. Relatively safe is the biopsy of the donor duodenum mucosa.Objective: to evaluate the efficacy of morphological examination of the donor duodenum mucosa in early diagnosis of an acute rejection crisis of pancreas graft.Material and methods. The study presents a retrospective analysis of 35 donor duodenum mucosa biopsies performed in 19 recipients. In order to assess the correlation between clinical and morphological signs of rejection, the patients were divided into two groups. The first group included 6 patients with clinical signs of graft dysfunction; the second group included 7 patients without signs of rejection. Statistical processing of the study results was made using the descriptive statistics methods.Results . The signs of immunological complications were identified in 18 donor duodenum mucosa biopsies (51.4%) in 12 recipients (63.2%). In most cases (n = 13; 72.2%), the histological signs of mild rejection were found, the signs of moderate and severe rejection were less frequent (n = 3; 16.6% and n = 2; 11.1%, respectively). Morphological signs of acute rejection were found in all the patients of the 1st group (n = 6), including the signs of mild rejection in 4 cases (66.6%), of medium and severe rejection in 1 case each (16.7%). In the 2nd group, morphological signs of mild rejection were found in 3 patients (42.9%). Differences between the groups in the incidence of immunological complications were statistically significant (p < 0.05).Conclusions: the biopsy of donor duodenum mucosa is an important criterion in the diagnosis of an acute rejection crisis of the pancreatoduodenal complex, and also remains a safe method, even in the earliest postoperative period.